Synthesis, anti-microbial, toxicity and molecular docking studies of N-nitroso-N-phenylhydroxylamine (cupferron) and its derivatives. (15th November 2021) - Waziri, Ibrahim; Isa, Mustafa A.; Sonopo, Molahlehi; Williams, D. Bradley G.; Muller, Alfred
Graphical abstract: Highlights: Cupferron and derivatives are readily synthesised and fully characterised. All compounds tested against Gram-negative and Gram-positive bacteria. Zone of inhibition studies show good activity against Gram-positive bacteria. Minimum inhibitory concentration study shows MIC as low as 2 µg.mL −1 . The compounds show less toxicity against healthy cell lines and molecular docking study displayed good interaction. Abstract: Bacterial resistance to antimicrobial agents is increasing at an alarming rate globally and requires new lead compounds for antibiotics. In this study, N -phenyl- N -nitroso hydroxylamine (cupferron) and its derivatives have been synthesised using readily available starting materials. The compounds were obtained in high yield and purity. They show activity towards a range of Gram-positive and Gram-negative pathogenic bacteria, with minimum inhibitory concentration (MIC) values as low as 2 μg.mL −1 against the tested organisms, especially for Gram-positive species. Toxicity studies on the lead compound 3b indicate insignificant effects on healthy cell lines. Molecular docking studies on the lead compound identify possible binding modes of the compound, and the results obtained correlate with those of in vitro and MIC studies. The lead compound shows excellent drug-likeness properties.